Fratura de fêmur: suas peculiaridades no paciente idoso e implicações no serviço de saúde no município de Belém/PA - OLIVEIRA, Marden Cravo de (2023)
Longevity became common in several countries and according to the Brazilian Institute of Geography and Statistics (IBGE), between the years 2005 and 2015, the Brazilian elderly population increased from 9.8% to 14.6%, a growth of 4.8%, showing elevation of the elderly population. The estimate of population aging can reach 2060, at a percentage above 25%. The aging process is marked by pathological incapacity and ollness (senility). This generates sensomotor, cognitive and psychosocial alterations, making the elderly more vulnerable to falls and domestic accidents. The occurrence of fractures in the alderly is related to greater bone fragility resulting from osteoporosis and to a greater tendency for falls that they usually present. These falls usually occur in the home environment and have several predisposing factors, being the most frequent yhe diverse neurological disorders, the use of medicines that affect the balance, greater muscle dificit and the presence of arthopathies and deficiences due to different diseases. Among fractures caused by domestic accidents, femoral fracture prevails, being more frequent after 60 years. These numbers are alarmed, since approximately 100 thousand fractures occur in Brazil each year, according to SUS’s computer department (DATASUS). This index tends to grow, because “the aging population generates an increase in the absolute number of hip fractures every year”. This work is a reptrospective and descriptive epidemiological study of a historical series from 2009 to 2018, in the city of Belém, PA, supported by scientific articles, and aims to present a panorama of the hospitalizations of elderly people with femur fracture in the last decade. In this context, hospitalizations of patients with femoral fractures presente a higher tendency in the more advanced age groups, as well as a predominance of the number of female patients, in males, in eldrely patients. Also, it is noticed that, the average time of hospitalization becomes greater as the age groups advance, becoming stable after 30 years. Also, it is verified that the costs for elderly patients represent an important part f the expenses with treatment of femoral fractures.